China's Belt and Road Initiative : A Geopolitical and Geo-Economic Assessment (The International Institute for Strategic Studies, 2022)
The IISS Strategic Dossier China's Belt and Road Initiative provides a geopolitical and geo-economic assessment of President Xi Jinping's flagship foreign-policy initiative. The dossier explores the Belt and Road Initiative's role in China's domestic industrial strategy and in the country's growing influence around the world. It studies how Beijing's ambitions, management and financing of the initiative have evolved since its launch in 2013. In addition, the volume reflects on the future of China's initiative following the COVID-19 pandemic. The dossier is organised around a region by region assessment of what Beijing has sought to achieve in different countries and how the Belt and Road Initiative has played out over time. The volume examines recipient countries' responses to the Belt and Road Initiative and how these have affected it. It also looks at responses from other global and regional powers to China's economic activities around the world and offers thoughts on ways the West might better contend with Beijing's geo-economic influence